How can EPR spectroscopy help to unravel molecular mechanisms of flavin-dependent photoreceptors? - Nohr, Daniel; Rodriguez, Ryan; Weber, Stefan; Schleicher, Erik (Frontiers in Molecular Biosciences, 2015)
Electron paramagnetic resonance (EPR) spectroscopy is a well-established spectroscopic method for the examination of paramagnetic molecules. Proteins can contain paramagnetic moieties in form of stable cofactors, transiently formed intermediates, or spin labels artificially introduced to cysteine sites. The focus of this review is to evaluate potential scopes of application of EPR to the emerging field of optogenetics. The main objective for EPR spectroscopy in this context is to unravel the complex mechanisms of light-active proteins, from their primary photoreaction to downstream signal transduction. An overview of recent results from the family of flavin-containing, blue-light dependent photoreceptors is given. In detail, mechanistic similarities and differences are condensed from the three classes of flavoproteins, the cryptochromes, LOV (Light-oxygen-voltage), and BLUF (blue-light using FAD) domains. Additionally, a concept that includes spin-labeled proteins and examination using modern pulsed EPR is introduced, which allows for a precise mapping of light-induced conformational changes.